METAPHOR, COGNITION AND CULTURE IN ENGLISH AND UZBEK IDIOMATIC COMPOUNDS: A COMPARATIVE COGNITIVE-LINGUISTIC STUDY - Amanova Baxtiniso Khamroevna (International Journal of Literature and Language Studies, 2026)
Idiomatic compounds represent complex lexical constructions in which meaning formation goes beyond the literal combination of individual components and involves cognitive mechanisms. This study investigates the formation of figurative meanings in English and Uzbek idiomatic compounds from a comparative linguo-cognitive perspective. Using cognitive-semantic and comparative analysis, the research examines the role of conceptual metaphor, metonymy, conceptual integration, and cultural cognitive models in meaning construction. The findings reveal that idiomatic compounds in both languages are systematically motivated rather than arbitrary formations. Conceptual metaphor appears as the dominant mechanism, particularly in expressions related to personality, emotions, intelligence, and social behaviour. Although English and Uzbek share universal cognitive patterns based on human experience, they demonstrate culture-specific differences in conceptual representation. The study contributes to comparative cognitive linguistics by explaining how language, cognition, and culture interact in the development of idiomatic meanings across different linguistic systems.